Back Cover Image, Volume 1, Issue 1, January 2022. Issue 1 (30th January 2022) - Unknown
Abstract : Back Cover : By designing the nanorod heterojunction arrays as active layer and adopting the strategy of maximum energy conversion performance, the problems of weak light absorption and poor carrier transport of solar cells can be effectively solved. In article number 20210008, Fen Qiao and co‐workers have reviewed design strategies of ZnO heterojunction arrays towards effective photovoltaic application.